Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 4 - Polynomials - Connecting: The Concepts - Exercises - Page 243: 3



Work Step by Step

Use the rule $\dfrac{a^m}{a^n}=a^{m-n}$ to obtain: $\dfrac{x^{-4}}{x^{10}} = x^{-4-10} = x^{-14}$ Use the rule $a^{-m} = \dfrac{1}{a^m}, m \gt 0$ to obtain: $x^{-14}=\dfrac{1}{x^{14}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.